Konstruksi Internalisasi Perubahan Budaya Pernikahan Melalui Media Sebagai Pertarungan Modal Sosial Kelas Ekonomi Menengah - Koesanto, Stefani Made Ayu Artharini (Dharma Duta, 2022)
The purposed of this research is to find how the construction of wedding cultural change phenomenon of middle low economic class society in Palangkaraya internalized through media. This research applies Pierre Bourdieu's reproduction of culture, Berger-Luckman’s construction of social reality, Veblen's emulation and global media concept as the framework. The Paradigm used in this research is constructionism and qualitative research which held in Palangkaraya. Depth interview and observation are used as data collection technique. This research has succeeded to explain the connection between social construction of reality on marriage and social struggle in the field of wedding with the influence of mass media in the wedding cultural change phenomenon for middle low economic class in Palangkaraya.